The Valentine that ate my teacher - Marney, Dean, 1952- (New York : Scholastic, 1998)
Strange things start happening to Lizzie and her friends on Valentine's Day, and when their substitute teacher disappears, they all have to work together to try and find him.
"An Apple paperback."
5.5
3-6
3-6
610
Keywords: Valentine's Day -- Fiction; Substitute teachers -- Fiction; Valentine's Day -- Fiction; Substitute teachers -- Fiction